Direct Control of Pt Film Orientation for Growth of (100)-oriented PZT Films - Quoc Trinh, Bui Nguyen (VNU Journal of Science: Mathematics - Physics, 2023)
We investigated highly (100)-oriented PZT films directly grown on Pt films coated on RuO 2 /SiO 2 /Si substrates via sputtering method. By controlling the preferred (100) orientation volume of the Pt films, we confirmed the effectiveness of high (100) orientation of Pt films suitable for the growth of highly (100)-oriented PZT films. Particularly, as the (100) orientation region of Pt film is larger than 90%, the PZT film with 95% of (100) orientation region can be formed, without using any seed layer as well as epitaxial growth process. We found that a highly (100)-oriented PZT film possesses large grains with a size of 150 nm, and it possesses twice remanent polarization of 58 m C/cm 2 and coercive electric field of 148 kV/cm with the relatively low leakage current less than 10 -6 A/cm 2 at the applied voltage of ± 4 V. One can convince that the technological process for highly (100)-oriented PZT films is simple, and it is promising for ferroelectric and piezoelectric applications in wide ranges.